Refugee entrepreneurship: resolving multi-contextuality and differential exclusion - Yetkin, Ugur (Journal of business ethics, 2024)
This study examines the multi-contextual dynamics of refugee entrepreneurship through the lens of embeddedness. It attempts to explain the interplay of inclusion and exclusion within a host society. For this purpose, the study qualitatively analyses the narratives of 39 Syrian refugee entrepreneurs and four critical informants in Türkiye. Our findings reveal a diverse set of refugee entrepreneurs, categorized into survival, ethnic-targeting, and integrating entrepreneurs, based on their motivations and level of embeddedness. Interestingly, as refugee entrepreneurs become more embedded in the host country, they experience increased exclusion due to various societal factors. To navigate these challenges, entrepreneurs continually negotiate their societal position using innovative strategies to combat exclusion. Our study incorporates social, political, institutional, and spatial contexts across host, home, and third countries. Thus, it extends the embeddedness literature by highlighting refugee entrepreneurs' multi-layered and multi-locational embeddedness. Our findings also emphasise the significant role of political embeddedness, which Research often overlooks. Differentially excluding refugee entrepreneurs from society and their counter-strategies are closely tied to their limited political embeddedness. Finally, we discuss the ethical and policy implications of promoting the inclusion of refugee entrepreneurs and contributing to the United Nations' Sustainable Development Goals. We argue that clear integration policies, removal of institutional barriers, and international cooperation are necessary.